Internacionalização da educação superior e o desenvolvimento de competências : perspectivas docentes em distintos contextos - Baranzeli, Caroline (2021)
One of the biggest Higher Education challenges is the connection between professional qualification and training through and for research. Globalization and internationalization processes impacted on HEIs actors and bring the discussion about the development of intercultural competencies. This work aims to understand how academics, from different contexts, understand internationalization processes and which competencies they consider essential for acting in the university context. The research drawn used multiple case studies in two institutions of Higher Education – one in the British context and the other in the Brazilian context. For that, 14 interviewees were carried out, with professors from both contexts and analysis was produced following the criteria of Discursive Textual Analysis and categorization of competencies, pointed out by the professors, from the perspectives of UNESCO. The results of the Brazilian case study points to a relation to the theme of internationalization, they talk about its possibilities, but mainly about the challenges imposed on the Brazilian reality. With regard to the skills needed to work in the research, teaching and extension axes, Brazilian academics point out as fundamental the lines presented by UNESCO, such as learning to be and to learn to live together. In the British context, it was observed that academics dominate the theme of internationalization, but their focus on issues such as student mobility demonstrates how national and institutional realities impact perceptions of internationalization. Regarding competencies, British academics also point out as fundamental the perspectives of learning to be and live together. It is pointed out that, despite the existing differences between the analyzes of both contexts, it is possible to observe the convergence of importance of the competencies of learning to be and living together for all academics.